An investigation on magnetic properties and electrical resistivity of nanocrystalline CoFeNi thick films synthesized through stabilized bath - S. Mehrizi; Mohammad Jafar Molaei; M. Heydarzadeh Sohi (Journal of Materials Research and Technology, 2022)
In this research, CoFeNi thick films were prepared through the electrodeposition process from a natural pH bath containing the complex agent of sodium citrate. By increasing applied current density, there is a transition from BCC (Fe) phase to BCC (Fe) + FCC (Co) phases and then to FCC (Co) phase. The XRD pattern showed a nanocrystalline structure for the CoFeNi thick films which was further confirmed by the TEM images. The magnetic properties of the synthesized magnetic films exhibit a noticeable decrease in the coercivity by decreasing the crystallite size which is consistent with the “D6” law. The resistivity of the CoFeNi thick films increased by decreasing the grain size which is due to the scattering of the charge carriers. The increase in the applied current density results in the gradual substitution of the iron atoms in CoFeNi films by nickel atoms leading to a reduction in saturation magnetization.